The Role of Leadership Styles on Employee Commitment of Czech-based Companies - Naghiyev, Farid; Martínez Pantoja, Yadira Ixchel; Escobar Rios, Andrea; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The study assesses the role of transformational, transactional and laissez-faire leadership styles on the employee commitment in Czech-based technological organizations such as SITA, IBM, SAP, and Accenture. By employing the combination of the Multifactor Leadership Questionnaire (MLQ) and Organizational Commitment Questionnaire (OCQ), the data gathered from 210 respondents was examined through the descriptive statistics and correlation analysis. Findings revealed that perception of leadership styles ranged from neutral to moderately positive in comparison to organizational commitment scoring neutral values. Based on the Pearson's correlations analysis, there was observed weak relationship between leadership styles and organizational commitment in reported organizations. The provided hypotheses of the research were rejected.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses